Exame Nacional do Ensino Médio: um estudo sobre a matemática financeira nas provas de matemática (1998-2023) - Vieira, Kaynan Casali (2024)
This study aims to analyze concepts, representations and situations present in Mathematics questions in the National High School Exam (Enem) tests. To this end, a qualitative perspective is adopted and the principles of content analysis are used. In the pre-analysis, initially, the documents were chosen, that is, the yellow notebooks from the Enem tests from 1998 to 2023. Subsequently, to select the questions, 18 terms were listed that are related to Mathematics Finance (MF) and cover social, economic and financial aspects. In order to allow verbal and nominal inflections, the prefixes were used: aplic, compr, consum, cust, descont, desp, financ, gast, invest, juro, lucro, mens, pag, rend, rent, salar, valor and vend. These searches totaled 383 occurrences in 123 different questions, of which only 15 belong to Enem (1998-2008) and the rest to the Mathematics and its Technologies tests of the New Enem (2009-2023). When exploring the material, the categories that emerged were created through the identification of recording units, listed when rereading the statements of the 123 questions, in order to carry out a coding of the raw data by cutting, aggregation and enumeration, considering three elements: concepts (phenomena that characterize the understanding and/or definition of something within the scope of School Mathematics), representations (records mobilized in statements and alternative answers to questions) and situations (scenarios in which problems are contextualized). Finally, in the last phase of content analysis, the 123 questions were classified into 36 categories grouped in relation to the three elements. Regarding concepts, eight categories were created, with 43,08% of the total questions exploring elementary operations involving the monetary system without using percentages and only 9,75% of the total having a greater association with MF characteristics and subjects, such as simple interest, compound interest and amortization systems. In relation to representations, 12 categories were identified, being that: all of them contain records in natural language and numeric and only 39,83% of the total questions contain exclusively these two forms; they also contain other records such as graphs (21,13%), tables (16,26%), icons (1,62%), algebraic expressions (13%) and geometric figures (3,25%) all accompanied by their respective quantity of questions; It is also noted that six categories highlight greater variation from the point of view of representations, as each one presents four distinct records, but only has one question classified in each, bringing together 4,87% of the total. With regard to situations, 16 categories were composed, of which 47,97% of the total questions address economic aspects, 41,46% involve financial aspects and 10,57% highlight social aspects; It should also be noted that in the first the category that received the largest number of questions was “cost of a good or service”, in the second “additional and discount” and in the third “salary remuneration”.